HUBUNGAN PENYAKIT KRONIS DENGAN MASALAH PSIKOSOSIAL PADA PASIEN DI RSUD GUNUNG JATI CIREBON - Endah Sari Purbaningsih (Jurnal Kesehatan Mahardika, 2018)
Any disease suffered by every human being will be perceived by humans as an affliction to the psychological and social consequences of humans. Psychosocial aspects are very important to be taken into account because a journey of chronic illness makes the patient feel that he has no hope, feelings of fear, anxiety, frustration, no power until feelings of anger arise in him. The purpose of this study was to determine the relationship of Chronic Disease with Psychosocial Problems in patients at Gunung Jati Cirebon Hospital. This research uses descriptive correlational method with Cross Sectional approach. The sampling technique that will be used in this study uses purposive sampling technique 61 respondents. Using the Kuesinoer Depression Anxiety Stress Scale (DASS), the statistical analysis technique used was the Chi Square analysis model. The results of the study explained that the most chronic disease suffered by respondents was DM (32.8%), most of the respondents had moderate category psychosocial problems as many as 37, there was a relationship of Chronic Disease with Psychosocial Problems in patients at Gunung Jati Cirebon Hospital with p value = 0,000 (at α = 0,05) or p value <α. the suggestion that researchers can convey is that they can carry out community service activities by conducting cognitive behavioral therapy in patients with chronic diseases to prevent psychosocial disorders and as support for patients with chronic diseases.